1987
DOI: 10.1159/000215749
|View full text |Cite
|
Sign up to set email alerts
|

Release of Plasminogen Activator by Batroxobin

Abstract: In the isolated perfused pig ear, batroxobin caused a dose-dependent increase in the release of plasminogen activator. The activator-releasing effect required the presence of the active enzyme. The activator released was of the tissue-type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Our results showed that patients with systemic bleeding presented increased levels of FDP, as well as decreased levels of plasminogen and alpha 2-antiplasmin, when compared to those without bleeding. B. atrox venom could be acting directly on fibrin and fibrinogen resulting in the generation of fibrinolysis products, and indirectly inducing the release of tissue plasminogen activator [ 6 , 15 , 38 , 39 ]. Also, the capacity of B. atrox venom to induce factor XIII activation [ 14 ], and intravascular thrombin generation [ 30 ] can contribute to the formation of intravascular cross-linked fibrin polymer and D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that patients with systemic bleeding presented increased levels of FDP, as well as decreased levels of plasminogen and alpha 2-antiplasmin, when compared to those without bleeding. B. atrox venom could be acting directly on fibrin and fibrinogen resulting in the generation of fibrinolysis products, and indirectly inducing the release of tissue plasminogen activator [ 6 , 15 , 38 , 39 ]. Also, the capacity of B. atrox venom to induce factor XIII activation [ 14 ], and intravascular thrombin generation [ 30 ] can contribute to the formation of intravascular cross-linked fibrin polymer and D-dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Batroxobin, the TLE from B. moojeni venom, has been reported to cause a dosedependent increase in the release of t-PA from an isolated perfused pig ear preparation [84]. In an additional report, a TLE habutoxin from Trimeresurus flavoviridis venom stimulated bovine pulmonary artery endothelial cells to release increased levels of u-PA and Plg activator inhibitor (PAI) [85].…”
Section: Snake Venom Plasminogen Activators (Pas): Structural and Biomentioning
confidence: 99%
“…Experimental data of coagulation parameters analysis demonstrated that recombinant batroxobin has no significant influence on other coagulation factors. Snake venom thrombin-like enzymes such as batroxobin, crotalase and ancrod were known to have not only potent procoagulant activities but also defibrinogenating activities, which are associated with the reduction of fibrinogen level in plasma by clearing converted fibrinogen and enhancing fibrinolytic activity [9,10,[32][33][34]. Recombinant and native batroxobins also decreased fibrinogen concentration in rat plasma (Fig.…”
Section: Effects Of Recombinant Batroxobin On Coagulation Parametersmentioning
confidence: 99%